BOOSTING STUDENTS' IDEAS THROUGH TEXT MODELLING: A CLASSROOM ACTION RESEARCH ON DISCUSSION WRITING - Fajriah, Yustika Nur; Rachmani, Rafsya; Vinh, Hoang Thi Tuong (University of Kuningan, 2025)
This study explores the use of Modeling of the Text (MoT) within the Genre-Based Approach (GBA) to enhance students' ability to construct well-supported arguments in discussion texts. Despite the recognized potential of MoT as an explicit teaching method, it remains underexplored in academic research. This Classroom Action Research, conducted over two cycles, involved 39 students, with a focus on 6 participants from a senior high school in West Java, Indonesia. Data were collected through classroom observations and text analysis. Findings from Cycle 1 indicated that while students were familiar with the structural components of discussion texts, they struggled with developing arguments, integrating evidence, and formulating a clear stance. However, in Cycle 2, the introduction of Toulmin’s Argumentation Model, counter-argument practice, and explicit teaching led to significant improvements in their writing. These interventions helped students construct more coherent arguments, engage in critical reasoning, and incorporate supporting evidence more effectively. Based on these results, the study advocates for teaching approaches that go beyond structural awareness to include targeted instruction on argumentation strategies, stance formulation, and the integration of research and digital literacy skills. Additionally, it suggests adopting differentiated instruction to address diverse student needs. The study concludes by recommending further research to examine the long-term effects of these instructional strategies on students’ writing proficiency.